ANALISIS PERANCANGAN SISTEM KONTROL DAN MONITORING BERBASIS ARDUINO UNO VIA INTERNET PADA PEMANFAATAN AIR KONDENSAT PADA KULKAS - Bagja, M. Fathan Sugih; Tamaji (Universitas Widya Kartika Surabaya, 2024)
Condensate water is a water which is resulted from the condensation process, usually thrown away regardless of its use. In this journal, a control system for the refrigeration system for the utilization of condensate water will be analyzed. This design includes the design of a cabin temperature control system and an automatic condensate water spraying control system.Arduino UNO will be used as controller and DS18B20 sensor will be used as a detector and also as a feedback. In addition, the monitoring system is designed to use laptop, LCD and smartphone screens with the ThingSpeak application. The result is the designed on-off control system be able to maintain the cabin temperature at the setpoint of 4.5oC. But there are still errors in the range of 0.12oC-0.13oC. Meanwhile, in the condensate water spraying control system, the spraying automatically turns on when the condenser exit temperature exceeds the setting temperature of 39oC, with an error in the range of 0.1oC-0.44oC. In addition, the monitoring system on ThingSpeak and LCD produces temperature graphs with values and patterns which be the same. Furthermore, the actual COP of the refrigeration system which fluctuates at value of 3.28 is greater than the actual COP without spraying which fluctuates at value of 2.95. This is shown by a graph of the actual COP with sprays which be higher at any time. The electric power of the refrigerator with spraying (104 W) is slightly lower than the system without spraying (114 W).